Correlation between microplastic disperse in sea and microplastic contained within fish’s gut organ system of semi-arid coastal beach, Kupang city, 2022 - Gregorius Kenang Widyantoro; Christina Olly Lada; Prisca Deviani Pakan; Listyawati Nurina (Indonesian Nutrition Association, 2022)
The product of marine resources, such as fish, are one of the sources of nutrition for local communities on the coastline of kota Kupang. Microplastics pollute the surroundings and human food sources, especially the marine environment, therefore, it could risk aggravating the state and quality of human health in direct proximity to the contaminated.